2022
DOI: 10.1159/000526636
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of Birdshot Uveitis after Stopping Immunosuppressive Treatment and Starting Immune Checkpoint Inhibitors for Lung Cancer

Abstract: A 56-year-old Caucasian woman with birdshot uveitis had to stop immunosuppressive treatment with adalimumab due to metastatic squamous lung carcinoma. She was subsequently treated with chemotherapy and pembrolizumab, an immune checkpoint inhibitor (ICI). After stopping adalimumab and starting pembrolizumab, the patient had an inflammatory relapse of birdshot uveitis with macular oedema. Birdshot uveitis is triggered by an unknown antigen presented on the HLA-A29 molecule which activates cytotoxic T-cells. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In a small retrospective study involving mostly melanoma patients, age and sex were not found to be significant risk factors, although premenopausal women (under age 52) were more likely to develop higher severity IRAEs and have their ICI treatment Few reports of birdshot-like uveitis induced by ICI therapy exist: our literature review yielded two case reports [157,158]. In the first instance, preexisting BU relapsed during pembrolizumab therapy-a 56-year-old Caucasian female, in the context of a new NSCLC diagnosis, had to discontinue her existing immunosuppressive therapy [158]. Eight months later, her ophthalmologist documented an increase in cystoid macular edema.…”
Section: Agementioning
confidence: 88%
See 2 more Smart Citations
“…In a small retrospective study involving mostly melanoma patients, age and sex were not found to be significant risk factors, although premenopausal women (under age 52) were more likely to develop higher severity IRAEs and have their ICI treatment Few reports of birdshot-like uveitis induced by ICI therapy exist: our literature review yielded two case reports [157,158]. In the first instance, preexisting BU relapsed during pembrolizumab therapy-a 56-year-old Caucasian female, in the context of a new NSCLC diagnosis, had to discontinue her existing immunosuppressive therapy [158]. Eight months later, her ophthalmologist documented an increase in cystoid macular edema.…”
Section: Agementioning
confidence: 88%
“…Few reports of birdshot-like uveitis induced by ICI therapy exist: our literature review yielded two case reports [157,158]. In the first instance, preexisting BU relapsed during pembrolizumab therapy-a 56-year-old Caucasian female, in the context of a new NSCLC diagnosis, had to discontinue her existing immunosuppressive therapy [158]. Eight months later, her ophthalmologist documented an increase in cystoid macular edema.…”
Section: Birdshot-like Posterior Uveitismentioning
confidence: 98%
See 1 more Smart Citation